Corrigendum to "The dissolution rates of simulated UK Magnox – ThORP blend nuclear waste glass as a function of pH, temperature and waste loading" [Miner. Mag. 79, (2015) 1529–1542]. (28th August 2018) - Corkhill, Claire. L.; Fisher, Adam J.; Strachan, Denis M.; Hand, Russell J.; Hyatt, Neil C.
Abstract: We revise the data fitting in our original paper [The dissolution rates of simulated UK Magnox - ThORP blend nuclear waste glass as a function of pH, temperature and waste loading, Miner. Mag. 79 (2015) 1529–1542]. The intrinsic rate constant data were calculated incorrectly, the corrected data are presented herein. To support the corrected analysis we have also taken the opportunity to report some additional 90°C data. The conclusions of the original paper remain sound.